Black-Box Testing pada Sistem Evaluasi Capaian Pembelajaran Berdasarkan Outcome Based Education - Yulherniwati; Hadi, Ronal; Asri, Ervan; Humaira; Febrian Kasmar, Andre (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
The implementation of outcome based education curriculla requires an evaluation system capable of objectively and systematically measuring the achievement of graduation learning outcomes (GLO). Therefore, comprehensive testing of the GLO evaluation system is essentially to ensure its reliability. This study designs functional testing using a black box-testing testing approach, employing techniques such as equivalence class partitioning, boundary value analysis and state transition testing. The test case design process follow the software testing process according to ISTQB, focusing on the initial three stages: planning, analysis and design. The findings indicate that this approach is effective in verifying the qualityof GLO evaluation system based on OBE. The resulting test case design can serve as a reference for subsequent testing stages, both manual and automated